Audit Disfungsional, Kompetensi, dan Independensi: Determinan Kualitas Audit: Studi Empiris pada Kantor Akuntan Publik di Wilayah Kota Semarang - Cherly Ayu Anggeraini; Arditya Dian Andika; Enny Susilowati Mardjono; Ngurah Pandji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the influence of dysfunctional audits, competence, and independence on audit quality among external auditors at a Public Accounting Firm (KAP) in Semarang City. The approach used is quantitative, with a survey method distributed through questionnaires to respondents selected using purposive sampling techniques. Data analysis was performed using multiple linear regression with SPSS. The results indicate that dysfunctional audits have a negative and significant effect on audit quality, while competence and independence have a positive and significant effect. Simultaneously, these three variables are also proven to have a significant effect on audit quality. These findings confirm that audit quality is influenced by behavioral factors, professional abilities, and the auditor's independence attitude.